A micro-cavity forming electrode with high thermal stability for semi-transparent colorful organic photovoltaics exceeding 13% power conversion efficiency. (February 2021) - Sung, Yun-Ming; Li, Meng-Zhen; Luo, Dian; Li, Yan-De; Biring, Sajal; Huang, Yu-Ching; Wang, Chun-Kai; Liu, Shun-Wei; Wong, Ken-Tseng
Abstract: In this study, we demonstrate a novel micro-cavity forming electrode with a sandwiched structure of Ag/HATCN/Ag. This new electrode presents high transmittance in visible wavelengths and reveals the capability of modulating the wavelength of transmitted light by precisely adjusting the thickness of HATCN interlayer. Notably, the Ag/HATCN/Ag electrode possesses excellent thermal stability that leads to an insignificant peak shift of the transmittance spectrum after thermal aging as exposed to air. This new electrode can be applied to both the solution-processed polymer solar cell (PSC) and thermally evaporated small molecule solar cell (SMSC). The implementation of the Ag/HATCN/Ag electrode for the blue, green, and red PSCs with PM6:Y6 as the photoactive blend results in the power conversion efficiency (PCE) over 13%, representing the highest performance for colorful PSCs ever reported. Significantly, the blue PSC shows the highest PCE up to 13.54% with a maximum transmittance of 15.6%. In addition, vacuum-processed red SMSC based on the active layer composed of DTDCPB:C70 blend shows a PCE and a maximum transmittance of 7.84% and 26.4%, respectively, while the blue and green SMSCs also exhibit PCE higher than 7%. The high PCE and the good transmittance of both the PSC and SMSC imply that the new micro-cavity forming Ag/HATCN/Ag electrode has promising potential in various practical applications. Graphical Abstract: A novel colorful electrode with micro-cavity structure of Ag/HATCN/Ag is proposed in this study which has not only high transmittance but also excellent thermal stability in air. This structure can be used as electrode in both PSC and thermal evaporated SMSC. The blue, green and red colored PM6:Y6 based PSC and DTDCPB:C70 based SMSC exhibit efficiency over 13% and 7%. ga1 Highlights: Micro-cavity-forming electrode Ag/HATCN/Ag was developed to control the transmission wavelength by changing HATCN thickness. The optimized cavity electrodes were applied to solution-processed and thermally evaporated colorful organic photovoltaics. The Ag/HATCN/Ag electrode possessed excellent thermal stability after thermal aging as exposed to air. All colorful devices showed similar performance regardless of the device color in different process organic photovoltaics.